Occurrence of diacetoxyscirpenol (anguidine) in processed cereals and pulses in Turkey by HPLC - BECEREN, AYFER (ELSEVIER SCI LTD, 2007)
The purpose of this study was to investigate the diacetoxyscirpenol (DAS, anguidine) level of contaminated cereal and pulse products in Turkey. DAS was detected using high performance liquid chromatography (HPLC) with diode array detector (DAD) at 205 nm and suspicious the results for two specimens suspected to contain DAS were confirmed by gas chromatography-mass spectrometry (GC-MS). An acetonitrile-water (21 + 4, v/v) extract of the samples was cleaned up on a column packed with alumina/charcoal (0.35 g + 0.40 g). The minimum detectable amount of DAS was 16 ng/injection, limit of detection was 0.8 mu g/g for HPLC. A total of 85.3% (SD 4.81, n = 5), 98.1% (SD 12.6 n = 5) and 96.4% (SD 3.2, n = 5), respectively. DAS was detected in none of the cereal and pulse products. (c) 2006 Elsevier Lts. All rights reserved.
Keywords: diacetoxyscirpenol; cereals; pulses; HPLC; T-2 TOXIN; FUSARIUM-SPOROTRICHIOIDES; TRICHOTHECENE MYCOTOXINS; LIQUID-CHROMATOGRAPHY; GRAINS; FOODSTUFFS; PRODUCTS; ORIGIN; MAIZE; FEEDS